Pengaruh Variasi Geometri Crash Box 2 Segmen terhadap Kemampuan Menyerap Energi Impak dengan Simulasi Komputer - Awali, Jatmiko; Choiron, Moch. Agus; Irawan, Yudy Surya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Crash box is a passive safety system placed on four wheeled vehicle, the purposes it to absorb the impact energy due to bumper no longer able hold the impact happened. There have been many studies done with the type of segment, so it needs development especially segment additional, and in this study of two segments of crash box is expected to absorb more energy, the additional of this segment purposes to increase the critical load so can be reduced the buckling. The method in this study used is ANSYS Workbench 14.5 finite element software. The variables used are the section type crash box geometry of circle, square, and hexagon, with cross section area of 1492 mm2, 1771 mm2, and 2045 mm2 and uniform height of 100 mm, the material used is aluminum AA 7003-T7. Simulation process begins when the impactor collision with speed 16 km/hour. From the research result is that moment inertia of the cross section area were able an important role in the absorption of impact energy, the cross section area 2045 mm2 were able to absorb the higher energy for each type of crash box, and the section of hexagon term that can absorb highest impact energy.Keywords: Crash Box, Simulation, Energy, Section, Two Segments